Examen especial a la cuenta de costos y gastos para determinar el sustento del resultado por el periodo 2014 de la empresa Construcciones Metálicas en la ciudad de Riobamba. - Benalcazar Tapia, Edison Javier (2016)
The present research work with subject Special examination to the account of the costs and expenses to determinate the sustenance of the result during 2014 of the company of metallic constructions in the city of Riobamba; This allowed to determine the degree of the reasonableness of the Balance Sheet, as well as the income statement, helping a correct decision making in order to correct certain errors present within it. The methods used for this research were interviews, direct observations and the methodology of the audit through which the results were obtained that will be of benefit to the entity. The special examination carried out on the cost and expenses account is part of the income statement, which will constitute a support tool for the manager and employees of the company, under this analysis it is concluded that there are shortcomings, one of the company. At the end of this special review, new guidelines could be established to improve the processes and development of the entity, thus helping to apply goo and new methods of work.